Hornbill abundance and breeding incidence in relation to habitat modification and fig fruit availability - Pawar, Pooja Yashwant; Mudappa, Divya; Raman, T. R. Shankar (Dryad, 2021)
Asian hornbills are known to forage and breed in fragmented rainforests
and agroforestry plantations in human‐modified landscapes adjoining
contiguous protected forests. However, the factors influencing year‐round
hornbill abundance, demography and tracking of key food resources such as
wild fig Ficus fruits in modified habitats and protected forests remain
poorly understood. We carried out monthly surveys of two species of high
conservation concern, the Vulnerable Great Hornbill (GH, Buceros bicornis)
and the endemic Malabar Grey Hornbill (MGH, Ocyceros griseus) for 15
months and monitored ripe fig fruit availability for 12 months along 11
line transects (total length 24 km) in shade‐coffee plantations and
adjoining continuous rainforests in a protected area (PA) in the Anamalai
Hills, Western Ghats, India. Both hornbill species used plantations and
the PA year‐round but distance sampling density estimates were higher in
the PA in both nesting (GH by 57%; MGH by 50%) and non‐nesting (GH by 53%;
MGH by 144%) seasons. Relative to estimates from 2004 to 2005, mean GH
density appeared stable or increasing, whereas MGH had declined by 39% in
the PA and by 56% in plantations. Monthly encounter rate of both hornbills
tended to be higher in the PA and that of MGH was also positively related
to the density of fig trees with ripe fruit. Sex ratios of observed adult
birds in the non‐nesting season were relatively even (GH) or slightly
female‐biased (MGH), but became male‐biased in both species during the
nesting season when females were confined in tree‐cavity nests. We used
change in the adult sex ratio of observed birds from the non‐nesting to
nesting season to estimate an index of the proportion of adult pairs
breeding at any point within the season, providing the first such
estimates for any hornbill species. The proportion of breeding pairs was
higher in the PA (GH – 56%, MGH – 64%) than in the plantations (GH – 33%,
MGH – 30%). Although hornbills use shade‐coffee plantations year‐round,
partly due to fig fruit availability, differences in hornbill density and
breeding incidence, as assessed from the sex ratios of observed adult
birds, indicate that plantations are a sub‐optimal habitat for both
species.
The data were collected as described in Pawar et al. (2020), Ibis
(https://doi.org/10.1111/ibi.12895). This includes hornbill observations
data from 11 line transects from the protected area (PA) and plantations
(see file: Sites.csv). It includes fig phenology monitoring data from belt
transect surveys as described in the publication.
The 01_ReadMe.txt file contains details of each column of data in the
following files that are included in the dataset. 02_Transects.csv:
Details of 12 transects, survey efforts in each season and habitat for two
hornbill species 03_Hornbill_observations.csv: Contains details of 778
hornbill encounters during the transect surveys, including habitats and
seasons 04_Hornbill_Distance.csv: Hornbill detections dataset from
transect surveys used as input for density estimation analyses using
Distance package in R 05_Ficus_phenology.csv: Tree-wise observation
dataset on fruiting phenology of figs from May 2017 to April 2018
06_HornbillGLM.csv: A consolidated input file including covariates data
used in the GLM analyses for both species of hornbills
Keywords: FOS: Natural sciences; Breeding; Bucerotidae; distance sampling; food availability; habitat alteration; habitat fragmentation; population estimates; resource tracking